Analisis Faktor yang Berhubungan dengan Kejadian Baby Blues Syndrom pada Ibu Nifas di Klinik Cempaka Medical Center Tambun Bekasi Tahun 2023 - Neti Yuhaeni; Eli Indawati (Malahayati Nursing Journal, 2024)
ABSTRACT At first glance, baby blues syndrome is not dangerous, but it has an impact on the development. The results of a preliminary study on 10 mothers stated that there was fear, anxiety, difficulty sleeping, crying, and worry if abnormalities occurred in their babies. This shows that the mother has baby blues syndrome. Knowing the analysis of factors associated with the incidence of baby blues syndrome in postpartum mothers at the Cempaka Medical Center Clinic Tambun Bekasi in 2023. This research is a quantitative analytic study with a cross sectional design. The sample in this study was made up of postpartum mothers who were one week postpartum at the Cempaka Medical Center Tambun Bekasi Clinic as of February 2023, totaling 63 respondents using the accidental sampling technique. The research instrument used was a questionnaire. Data is primary data analyzed using the square test. The results of univariate analysis showed that most postpartum mothers did not experience baby blues syndrome (63.5%), had readiness (77.8%), high husband support (82.5%), type of normal delivery (63.5%), good knowledge (77.8%), and planned pregnancy (69.8%). The results of bivariate analysis revealed that there was a significant relationship between mother's readiness (p value = 0.006), husband's support (p value = 0.013), type of delivery (p value = 0.026), knowledge (p value = 0.006), and pregnancy planning (p value = 0.042) and the incidence of baby blues syndrome in postpartum mothers. Maternal readiness, husband's support, type of delivery, knowledge, and pregnancy planning are related to the incidence of baby blues syndrome in postpartum mothers. It is hoped that midwives can increase the knowledge of mothers, husbands, and families by providing more intensive counseling to avoid baby blues syndrome in postpartum mothers. Keywords: Baby Blues Syndrome, Mother's Readiness, Husband's Support, Type of Delivery, Knowledge And Planning of Pregnancy, Postpartum Mother  ABSTRAK Sekilas baby blues syndrom memang tidak berbahaya, tapi berdampak terhadap perkembangan bayinya. Hasil studi pendahuluan pada 10 ibu menyatakan adanya rasa takut, cemas, waswas, susah tidur dan suka menangis setelah melahirkan dan khawatir jika terjadi kelainan pada bayinya. Hal ini menunjukkan bahwa ibu mengalami baby blues syndrom. Mengetahui analisis faktor yang berhubungan dengan kejadian baby blues syndrom pada ibu nifas di Klinik Cempaka Medical Center Tambun Bekasi tahun 2023. Penelitian ini merupakan penelitian analitik kuantitatif dengan rancangan cross sectional. Sampel dalam penelitian ini adalah ibu nifas satu minggu postpartum yang berada di Klinik Cempaka Medical Center Tambun Bekasi terhitung dari bulan Februari 2023 berjumlah 63 responden dengan teknik accidental sampling. Instrumen penelitian menggunakan kuesioner. Data merupakan data primer dianalisis menggunakan uji uji  square. Hasil analisis univariat diketahui sebagian besar ibu nifas tidak mengalami baby blues syndrom 63,5%, memiliki kesiapan 77,8%, dukungan suami tinggi 82,5,5%, jenis persalinan normal 63,5%, memiliki pengetahuan baik 77,8% dan kehamilan direncanakan 69,8%. Hasil analisis bivariat diketahui bahwa ada hubungan yang signifikan antara kesiapan ibu (p value = 0,006),  dukungan suami (p value = 0,013), jenis persalinan (p value = 0,026), pengetahuan (p value = 0,006) dan perencanaan kehamilan (p value = 0,042) dengan kejadian baby blues syndrom pada ibu nifas. Kesiapan ibu, dukungan suami, jenis persalinan, pengetahuan dan perencanaan kehamilan berhubungan dengan kejadian baby blues syndrom pada ibu nifas. Diharapkan bidan dapat meningkatkan pengetahuan ibu, suami dan keluarga dengan cara memberikan penyuluhan yang lebih intensif agar terhindar dari baby blues syndrom pada ibu nifas. Kata Kunci: Baby Blues Syndrom, Kesiapan Ibu, Dukungan Suami, Jenis Persalinan, Pengetahuan dan Perencanaan Kehamilan, Ibu Nifas